EXPLORING TRANSFORMATIONAL LEADERSHIP, LEARNING ORIENTATION, AND CREATIVE SELF EFFICACY ON EMPLOYEE CREATIVITY - Fuadiputra, Iqbal Ramadhani (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
Basically, from year to year, business always develops. This is what makes a transformational leader needed to be able to face the demands of the ever-changing market. This study itself discusses transportation service companies in Indonesia that have undergone massive changes and adjusted to market needs. One of the things that affects this is the learning orientation of the Institute as well as creative self-efficacy and work creativity. The purpose of this study proves that employee creativity encourages the organization to develop. This study uses the SmartPLS analysis method as analysis. The test results prove that Transformational Leadership has an impact on employee creativity in this company. In addition, why learning orientation has less impact on employee creativity is also explained in this study.